Improving Communication between Client and Contractor during Construction Project in Nigerian Construction Industry - Ishaq Muktar Ishaq; Roshartini Omar; Mohd Yamani Yahya; Norliana Sarpin (Journal of Technology Management and Business, 2019)
Abstract: Communication today has become the crucial element of every organisation. In construction industry, during construction project, information need to be accurately and timely communicating among project stakeholders in order to realized the project objectives. Poor communication between client and contractor during construction project is one of the major factors that affect project delivery. Therefore the objectives of this research are to investigate the causes and effects of poor communication between client and contractor and the suitable methods to improve communication between the client and contractor. The objectives where achieved by identifying the causes and effects of poor communication between client and contractor, and the methods to improve communication between the client and contractor in the Nigerian construction industry through a statistical analyses. Structured questionnaire was used to 120 combinations of clients and contractors in the construction industry with 80% of response rate. Several analyses such as frequency, mean, ranking and Regression were used to analyze the data. The results shows that, lack of corporation and selfish interest were the most causes of poor communication between the client and contractor. Contrastingly, maintaining integrity and sufficient trust were the most significant ways to improve communication between the client and contractor. The hypothesis reveals that, poor communication between the client and contractor has significant effects on construction projects. This research will profit the client and contractor, and the various project stakeholders in the construction industry, by providing adequate knowledge regarding the causes and effects of poor communication between the client and contractor, so that necessary steps to be taken for prevention. Also it will provide knowledge about the appropriate strategies (method) to employ in order to improve communication between the two parties. Keywords: Construction, Communication, Client, Contractor, Nigeria